A review of retention mechanism studies for packed column supercritical fluid chromatography. Issue 1 (21st January 2021) - Si‐Hung, Le; Bamba, Takeshi
Abstract: The packed column supercritical fluid chromatography has risen as a promising alternative separation technique to the conventional liquid chromatography and gas chromatography. Although the packed column supercritical fluid chromatography has many advantages compared to other chromatographic techniques, its separation mechanism is not fully understood due to the complex combination effects of many chromatographic parameters on separation quality and the lacking of global strategies for studying separation mechanisms. This review aims to provide recent information regarding the chromatographic behaviors and the effects of the parameters on the separation, discuss the results, and point out the remaining bottlenecks in the packed column supercritical fluid chromatography retention mechanism studies.